Islamic Securities Crowdfunding (I-SCF): A Potential Analysis of Sustainable Development Goals Based on Al-Maqashid Sharia’s Perspectives - Fadhila Dhiyaul Wafa; Irni Sri Cahyanti; Muhsin Muhsin (Universitas Syiah Kuala, 2022)
Objective –This research aims to analyze the potential of Islamic securities crowdfunding as an effort to create Sustainable Development Goals (SDGs) with an al-Maqashid Sharia perspective.Methodology –This research uses qualitative descriptive research methods to obtain a description or overview of the potential of I-SCF for the Sustainable Development Goals based on the perspective of Maqashid Sharia. It utilizes a literature study with a Maqashid Sharia perspective as the main reference.Results –Numerous studies show that sharia securities crowdfunding has the potential to strengthen MSME capital in the post-Covid-19 pandemic era, expand access to Islamic financial services for the community, create a profitable investment sector, and strengthen the halal industry. These potentials lead to the values of the purpose of Maqashid Sharia, which include the five main benefits (al-kulliyah al-khamsah).Research limitations –This research is limited to I-SCF in Indonesia hence subsequent studies may conduct further research on I-SCF in other countries for the purpose of comparisons. It also uses a quality-descriptive method hence future research may use quantitative analysis methods to provide a more specific picture of the influence on the SDGs.Implications - This research is important for the development and utilization of the potential of I-SCF in Indonesia. The study of Maqashid sharia on I-SCF shows that practically, I-SCF has maximum benefits for society without abandoning compliance with Islamic law.